РОССИЙСКАЯ ЕЖЕНЕДЕЛЬНАЯ ГАЗЕТА «ЗАВТРА» КАК ПРОПАГАНДИСТ ИМПЕРСКОЙ ИДЕОЛОГИИ - Szoszyn, Rusłan (Przegląd Rusycystyczny, 2016)
RUSS IAN WEE KLY NE WSPAPER “ZA VTRA ” AS A PROPAGAND IST OF IMPER IAL IDEOLOGY S u m m a r y The article is dedicated to various types of the imperial ideology in “Zawtra” magazine. Conducted analyses lead to conclusion, that the imperial ideology dominates in entire magazine’s writing content, not only in pieces about political affairs, but also about culture or even biographical reviews. The article is also an attempt of analyzing the magazine transformations starting form “perestroika” period till nowadays; from expressing an idea of “ the spirit opposition” to “the imperial ideology” of Russian state.